Synergistic Effect between Maternal Infection and Adolescent Cannabinoid Exposure on Serotonin 5HT1A Receptor Binding in the Hippocampus: Testing the "Two Hit" Hypothesis for the Development of Schizophrenia, - DALTON, VICTORIA (My University, 2012)
Infections during pregnancy and adolescent cannabis use have both been identified as environmental risk factors for schizophrenia. We combined these factors in an animal model and looked at their effects, alone and in combination, on serotonin 5HT1A receptor binding (5HT1AR) binding longitudinally from late adolescence to adulthood. Pregnant rats were exposed to the viral mimic poly I:C on embryonic day 15. Adolescent offspring received daily injections of the cannabinoid HU210 for 14 days starting on postnatal day (PND) 35. Hippocampal and cortical 5HT1AR binding was quantified autoradiographically using [3H]8-OH-DPAT, in late adolescent (PND 55), young adult (PND 65) and adult (PND 90) rats. Descendants of poly I:C treated rats showed significant increases of 15?18% in 5HT1AR in the hippocampus (CA1) compared to controls at all developmental ages. Offspring of poly I:C treated rats exposed to HU210 during adolescence exhibited even greater elevations in 5HT1AR (with increases of 44, 29, and 39% at PNDs 55, 65, and 90). No effect of HU210 alone was observed. Our results suggest a synergistic effect of prenatal infection and adolescent cannabinoid exposure on the integrity of the serotoninergic system in the hippocampus that may provide the neurochemical substrate for abnormal hippocampal-related functions relevant to schizophrenia.
PUBLISHED
Keywords: Neuroscience; Maternal Infection; Cannabinoid; Serotonin; Cannabis